Current Evidence and Insights about Genetics in Thoracic Aorta Disease - Gianluigi Bisleri; Lorenzo Bagozzi; Claudio Muneretto (The Scientific World Journal)
Thoracic aortic aneurysms have been historically considered to be caused by etiologic factors similar to those implied in abdominal aortic aneurysms. However, during the past decade, there has been increasing evidence that almost 20% of thoracic aortic aneurysms may be associated with a genetic disease, often within a syndromic or familial disorder. Moreover, the presence of congenital anomalies, such as bicuspid aortic valve, may have a unique common genetic underlying cause. Finally, also sporadic forms have been found to be potentially associated with genetic disorders, as highlighted by the analysis of rare variants and expression of specific microRNAs. We therefore sought to perform a comprehensive review of the role of genetic causes in the development of thoracic aortic aneurysms, by analyzing in detail the current evidence of genetic alterations in syndromes such as Marfan, Loeys-Dietz, and Ehler-Danlos, familial or sporadic forms, or forms associated with bicuspid aortic valve.